2015
DOI: 10.1007/s11695-015-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Antral Resection in Laparoscopic Sleeve Gastrectomy and its Relationship to Excess Weight Loss

Abstract: Radical antral resection in association with LSG safely potentiates the restrictive effect achieved and may result in greater and better maintained weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…Another retrospective study by Obeidat et al reported similar results although the group with antral resection was operated after the group of antral preservation (better experience and technique) (EL:3) [24]. This can be attributed to the higher intragastric pressure obtained after antral resection.…”
Section: Distance From the Pylorusmentioning
confidence: 85%
“…Another retrospective study by Obeidat et al reported similar results although the group with antral resection was operated after the group of antral preservation (better experience and technique) (EL:3) [24]. This can be attributed to the higher intragastric pressure obtained after antral resection.…”
Section: Distance From the Pylorusmentioning
confidence: 85%
“…В более поздние сроки, по данным отдельных авторов, частота рецидива ожирения может достигать 50 %. Напротив, другие исследования предоставляют более оптимистичные показатели -30 % [17,23].…”
Section: продольна я резекция же лудк аunclassified
“…Напротив, при расстоянии менее 4 см от пилоруса избыточная масса тела снижается на 75,5 %. Удаление всего антрального отдела желудка позволяет добиться редукции 81,5 ± 22,9 % избыточной массы тела с минимальной частотой рецидива ожирения (до 5 %) [17,21].…”
Section: продольна я резекция же лудк аunclassified
“…Laparoscopic sleeve gastrectomy (LSG) has still been the most frequently undergone bariatric procedure in TURKEY. The success of weight loss surgery is defined by the rate of excess weight loss (EWL) (1,2). Parameters which affect the excess weight loss percent is the subject of research (3)(4)(5).…”
Section: Inroduction Inroductionmentioning
confidence: 99%